Inhibitory effect of artemether on Propionibacterium acnes in vitro - Guojiang WANG; Xiangming CHEN; Wentong SHEN; Qin PEI; Haiqing ZHANG; Huiqiong HE (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective To explore the antibacterial effect of artemether on P. acnes in vitro and its effect on the bacterial morphology in order to provide a rationale for its use in the treatment of acne. Methods The minimal inhibitory concentrations (MIC) of artemether, doxycycline hydrochloride and their combination on P. acnes were determined by broth microdilution method, while the morphological changes of P. acnes were observed with a scanning electron microscope. Results The MICs of artemether and doxycycline hydrochloride were (117.19±76.15) μg/mL and (0.08±0.05) μg/mL, respectively. In the group of P. acnes treated with combination of artemether and doxycycline, MICs of artemether and doxycycline were (31.96±19.58) μg/mL and (0.02±0.01) μg/mL, respectively. The MIC of artemether differed significantly between artemether treatment alone and artemether combined with doxycycline (t=4.03, P<0.01). Under scanning electron microscope, the germ length differed significantly between untreated controls (19.80±3.08) μm and treated group (13.40±4.47) μm (t=5.04, P<0.01). The bacterial wall in the controls was smooth and stretched, while that in the treated group was rough and distorted. Conclusions Artemether inhibits P. acnes. Artemether and doxycycline have synergistic antibacterial effect, possibly via morphological alterations of cell walls of P. acnes. Artemether may be a candidate drug for acne treatment, and its combination with doxycycline can synergically inhibit P. acnes.